2022
DOI: 10.3390/nu15010062
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Management of Intestinal Failure due to Short Bowel Syndrome in Children

Abstract: Background: The most common cause of intestinal failure (IF) in childhood remains short bowel syndrome (SBS), where bowel mass is significantly reduced due to a congenital atresia or resection and parenteral nutrition (PN) needed. Home PN has improved outcome and quality of life, but the long-term therapeutic goal is to achieve enteral autonomy whilst avoiding long term complications. This paper is aimed at discussing nutritional strategies available to clinicians caring for these patients. Methods: A literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 79 publications
0
4
0
2
Order By: Relevance
“…One study reported that the strongest correlation with shorter duration of parenteral nutrition needs in neonates with short bowel syndrome was seen with breast milk 40 . This is thought to be modulated by the presence of immunological factors such as immunoglobulin A, leucocytes and nucleotides, anti‐inflammatory cytokines, growth‐factors, human milk oligosaccharides and microbiota 41,42 . Pasteurised donor breast milk has been increasingly used for preterm infants when maternal breast milk was not available.…”
Section: Resultsmentioning
confidence: 99%
“…One study reported that the strongest correlation with shorter duration of parenteral nutrition needs in neonates with short bowel syndrome was seen with breast milk 40 . This is thought to be modulated by the presence of immunological factors such as immunoglobulin A, leucocytes and nucleotides, anti‐inflammatory cytokines, growth‐factors, human milk oligosaccharides and microbiota 41,42 . Pasteurised donor breast milk has been increasingly used for preterm infants when maternal breast milk was not available.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it has been shown that the presence of nutrients in the intestinal lumen is a key factor promoting intestinal adaption and digestive autonomy, favoring the use of EHF, as it is more complex than AAF. Thus, some authors would recommend starting breastfeeding or even a formula with whole CMP, switching to an EHF if the previous one is not tolerated, and reserving the use of AAF if the EHF fails ( 81 , 82 ).…”
Section: Resultsmentioning
confidence: 99%
“…Case Report ного состояния, дефицит питательных веществ и витаминов, плохая прибавка в весе [1,4]. Энтеральное питание в физиологическом объеме невозможно, что требует нутритивной поддержки с использованием длительного парентерального питания (ПП) и туннельных центральных венозных катетеров (ЦВК).…”
Section: клинический случайunclassified
“…Основными проявлениями СКК и ХКН являются синдром мальабсорбции, белково-энергетическая недостаточность, нарушение баланса электролитов и кислотно-щелочного состояния, недостаточность микроэлементов и витаминов, задержка физического развития [4]. Адаптация кишечника после резекции представляет собой сложный физиологический процесс.…”
Section:  обсуждениеunclassified